Analysis and Minimization of Output Current Ripple of Multiphase Carrier-Based PWM Inverters - Pekik Argo Dahono (Institute for Research and Community Services, Institut Teknologi Bandung, 2010)
Analysis and minimization of output current ripple of multiphase carrier-based PWM inverters are presented in this paper. Analytical expression of rms value of output current ripple of multiphase PWM inverters as a function of the reference signal is first derived. Based on this expression, it is shown that a pure sinusoidal signal is the optimum reference signal that results in minimum output current ripple. Different to three-phase PWM inverters, injection of harmonics into the sinusoidal reference signal is neither necessary nor useful. The rms values of output current ripple of 5-, 7-, and 9-phase PWM inverters under various reference signals are compared. Experimental results are included to show the validity of the analysis method.